RESEARCH ON TEACHING STYLE PREFERENCES OF UZBEK UNIVERSITY TEACHERS - Tanzilla Artikova (Galaxy International Interdisciplinary Research Journal, 2023)
The purpose of this research is to examine the characteristics of the language teaching style preferences of Uzbek University teachers. A quantitative investigation was conducted for this study. Due to the Covid-19 outbreak, the data for the research was collected electronically from 90 teachers (48 males and 42 females) of the Department of English at Namangan State University, Uzbekistan, 2020. Reid’s Perceptual Teaching Style Preferences Questionnaire had been adopted for the research instrument. The researcher designed an online questionnaire on the Google Drive platform. Basically, the results were analyzed in the SPSS program.